Statistical Tests for the Order of a Regression Model Based on a Single Series of Observations - Shlepakov, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We construct a test for the determination of the order of a linear regression model on the basis of a single series of observations in the case of normally distributed noise with mean value zero and bounded variance. We propose a new equilibrium statistic for the model with infinite (but single) series of observations; by using this statistic, we construct a test for the determination of the order of this model.